The effect of prenatal exposure to music on fetal movements and fetal heart rate: a pilot study. (18th July 2021) - Brillo, Eleonora; Tosto, Valentina; Ceccagnoli, Andrea; Nikolova, Natasha; Pinzaglia, Valentina; Bordoni, Francesca; Spano, Filippo; Bini, Vittorio; Giardina, Irene; Renzo, Gian Carlo Di
Abstract: Objective: To assess and compare fetal cardiac parameters of fetuses listening to music before and during nonstress test, only during the test or never. Study design: Thirty healthy mother-fetus dyads were randomized in a 1:1:1 ratio to one of three groups: group A in which fetuses were submitted to prelistening phase (33rd + 0 to 36th + 3 week) and listening sessions during 4 nonstress tests, group B in which fetuses were submitted to listening sessions during 4 nonstress tests, and group C receiving 4 nonstress tests without any listening. We assessed mean fetal heart rate, fetal heart rate accelerations, fetal heart rate decelerations, fetal movements and uterine contractility. Results: Fetuses of the group A, who had already listened to a particular piece of music during previous sessions, had significantly increased their heart rate accelerations and movements during the music listening session of the last nonstress test. No significant changes were observed in the number of uterine contractions. Conclusions: Our findings show that fetuses slightly respond to that music they know, but they do not significantly respond to unknown music.